2020
DOI: 10.1111/1745-9133.12491
|View full text |Cite
|
Sign up to set email alerts
|

Examining the state repression‐terrorism nexus: Dynamic relationships among repressive counterterrorism actions, terrorist targets, and deadly terrorist violence in Israel

Abstract: Research Summary: This study assesses the impact of state repressive counterterrorism actions on terrorists' targeting and lethality of the terrorism landscape in Israel.Using systematic data on government responses to terrorism and an empirical model that addresses reciprocal relationships, we analyze dynamical interactions between types of government repression with attacks against civilian or government targets, and deadly terrorist violence. Contrary to public policy pronouncements of forcefully fighting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 136 publications
(187 reference statements)
0
2
0
Order By: Relevance
“…In support of backlash interpretations, the authors discovered that three of the six counterterrorist interventions used by the British during this period significantly increased the hazard of future terrorist strikes, two interventions had no significant effect in either direction, and only one found a short-lived deterrence effect. Similarly, Hsu and McDowall (2020) found that repressive counterterrorism actions increased violence in Israel, and that backlash effects were dependent on the magnitude of government repression, the target and the lethality of terrorist attacks.…”
Section: Rational Choice and Deterrencementioning
confidence: 96%
“…In support of backlash interpretations, the authors discovered that three of the six counterterrorist interventions used by the British during this period significantly increased the hazard of future terrorist strikes, two interventions had no significant effect in either direction, and only one found a short-lived deterrence effect. Similarly, Hsu and McDowall (2020) found that repressive counterterrorism actions increased violence in Israel, and that backlash effects were dependent on the magnitude of government repression, the target and the lethality of terrorist attacks.…”
Section: Rational Choice and Deterrencementioning
confidence: 96%
“…In attempting to synthesize the results, indiscriminate policies like widescale crackdowns appear to have no effect on future terror attacks, and if they do, it is more likely to be a backlash effect, whereby terrorism increases. This has been found across a variety of contexts (Argomaniz & Vidal-Diez, 2015;Hsu & McDowall, 2020; LaFree, Dugan & Korte, 2009). Conversely, in many of these very studies, policies conceptualized as representing 'soft' approaches are more likely to be associated with decreases in the risk of terrorism.…”
Section: Deterrence Of Terrorismmentioning
confidence: 97%
“…Considerable work has been done on exploring the mobilizing potential of grievances related to socioeconomic hardship [34], poor education [35], and lack of political representation [36]. There is also a rich tradition of scholarship looking at the role of (perceived) state repression, and the ways in which increasingly antagonistic interactions between states and non-state challengers, such as protest movements, can contribute to the outbreak of political violence [37][38][39][40]. Furthermore, scholars have taken an interest in transnational "spillover" effects, noting that conflict in one particular country or region can affect a geographically distant locale through diaspora links, or because overseas military interventions create an impetus for retribution [41,42].…”
Section: Researching Involvement In Terrorist Violencementioning
confidence: 99%